Direct brain recordings reveal occipital cortex involvement in memory development. (November 2020) - Yin, Qin; Johnson, Elizabeth L.; Tang, Lingfei; Auguste, Kurtis I.; Knight, Robert T.; Asano, Eishi; Ofen, Noa
Abstract: Processing of low-level visual information shows robust developmental gains through childhood and adolescence. However, it is unknown whether low-level visual processing in the occipital cortex supports age-related gains in memory for complex visual stimuli. Here, we examined occipital alpha activity during visual scene encoding in 24 children and adolescents, aged 6.2–20.5 years, who performed a subsequent memory task while undergoing electrocorticographic recording. Scenes were classified as high- or low-complexity by the number of unique object categories depicted. We found that recognition of high-complexity, but not low-complexity, scenes increased with age. Age was associated with decreased alpha power and increased instantaneous alpha frequency during the encoding of subsequently recognized high- compared to low-complexity scenes. Critically, decreased alpha power predicted improved recognition of high-complexity scenes in adolescents. These findings demonstrate how the functional maturation of the occipital cortex supports the development of memory for complex visual scenes. Highlights: Pediatric ECoG links occipital alpha activity to visual memory development. Recognition memory for complex visual scenes improves with age. Occipital alpha power predicts age-related gains in recognition of complex scenes. Occipital alpha frequency during encoding of complex scenes increases with age.